The influence of teachers' empowerment on teachers' organizational commitment in Sipitang secondary schools - Suffizan Kanik (2008)
The study aimed to explore the level of teachers' empowerment, the level of teachers' organizational commitment and the relationship between teachers' empowerment and the organizational commitment of teachers in Sipitang secondary schools as well as the difference between teaching tenure in present school and teachers' organizational commitment. The six dimensions of empowerment proposed by Short & Rinehart (1992) and the Organizational commitment model which was developed by Meyer and Allen (1991) served as the theoretical framework for the study. The six dimensions of empowerment are classifies as involvement in decision making, opportunity for professional growth, self efficacy, status, autonomy and impact. The organizational commitment on the other hand, is divided into affective commitment, continuance commitment and normative commitment. Data was obtained from 126 Sipitang's secondary schools teachers. Two questionnaires were used as the main instrument; Short & Rinehart (1992) School Participants Empowerment Scale (SPES) which is consisted of 38 items and Mowday, Steers & Porter (1979) Organizational Commitment Questionnaire (OCQ), which is consisted of 15 items. Pearson Correlation and One-way ANOVA analysis were use to analyze data by using SPSS for windows version 16.0. The findings obtained based on this study indicates that in general, secondary school teachers in Sipitang district show high level of empowerment and organizational commitment. The research also indicates that there is no significant difference between teaching tenure in current sc:hool and organizational commitment where F (df= 3, 120, p < .OS = .38). However, the finding of this study demonstrates that there is a positive and significant correlation between teachers' empowerment and teachers' organizational commitment (r = .467). This research also suggested numbers of strategies to improve teacher's organizational commitment and practical implications of the study that could help in the implementation of empowerment in school organization.